DESENVOLVIMENTO DE COMPÓSITOS POLIMÉRICOS DE POLIPROPILENO COM FIBRAS NATURAIS DE COCO E SISAL PARA APLICAÇÕES NO SETOR ELÉTRICO - Salum, Aline Souza (2014)
In this paper were developed polypropylene composites with coconut and sisal fibers for applications in the electric sector. The mechanical properties of composites with compositions containing from 5 to 40 % by weight of fibers, coupling agent and antioxidant were studied; and it was decided that would be used 10 % of fibers in the next formulations. Then, were studied the mechanical properties and flammability of the composites containing an UV stabilizer with flame retardant effect, aluminum trihydrate (ATH), antimony trioxide (Sb2O3), and an halogen free flame retardant additive in various amounts and was obtained a formulation with V2 classification, according to UL 94. Then three composites were formulated by increasing the amount of additives present in the formulation with V2 classification and added an impact modifier. Were then obtained a formulation with V0 classification and Izod impact resistance of (26.89 ± 1.89) J/m for composites with coconut fibers, and (25.35 ± 3.47) J/m for composite with sisal fibers.